Deposition amount effects on the microstructure of ion-beam-sputtering grown Mn0.03Ge0.97 quantum dots for spintronic applications. (11th January 2021) - Li, Yahui; Li, Chen; Tong, Haochen; Chen, Tao; Li, Guangyang; Huang, Shizhe; Tang, Shumin; Qiu, Feng; Yang, Jie; Sun, Tao; Yang, Yu; Wang, Chong
Abstract: Here, a relative simpler and lower cost method, ion beam sputtering deposition was applied to fabricate diluted magnetic Mn x Ge1− x quantum dots (QDs). The effects of Ge–Mn co-deposition amount on the morphology and crystallization of Mn0.03 Ge0.97 QDs were investigated systematically by employing the atomic force microscopy and Raman spectroscopy techniques. It can be seen that the morphology, density, and crystallinity of Mn0.03 Ge0.97 QDs exhibit unique evolution processes with the increase of Ge–Mn co-sputtering amount. The optimal deposition amount for realizing well size-uniform, large-aspect-ratio, and high-density QDs is also determined. The unique evolution route of diluted magnetic semiconductor QDs and the amount of co-sputtering are also discussed sufficiently.